Experimental investigation of an improved ejector with optimal flow profile - Xinyue Hao; Jiwei Yan; Neng Gao; Oleksii Volovyk; Yifan Zhou; Guangming Chen (Case Studies in Thermal Engineering, 2023)
The flow profile of the ejector directly affects the distribution of velocity and thermodynamic parameters such as pressure, temperature, and density, which are closely related to the internal irreversible loss of the ejector. This paper provides the performance investigation of an improved ejector with an optimal flow profile based on the Witozinsky curve for the first time. Faster contraction at the front part of the optimal profile helps to increase the fluid velocity, and slower contraction at the rear part could reduce the fluid fluctuation and boundary layer separation, which matches the fluid expansion better. It thus contributes to the reduction of irreversible internal losses and increases the efficiency of the ejector. Experiments were conducted under the same conditions to compare the performance superiority of the conventional and improved ejector. Results show that the entrainment ratio of the improved ejector could increase by as high as 19.2%. By testing the wall pressure distribution, the improvement of the entrainment ratio is attributed to the smaller velocity difference between the primary and secondary fluids at the nozzle exit. These results confirmed the potential application of the Witozinsky curve in ejector improvement and provided theoretical guidance for novel profile design.